230k views
3 votes
What is the solution of the equation 4(3-x)^4/3-5=59

User Haael
by
6.1k points

2 Answers

4 votes
The solution is x=5

User Shivam Bhusri
by
7.0k points
1 vote

Answer:

Given the equation:
4(3-x)^{(4)/(3)} -5 = 59

Add 5 to both sides we have;


4(3-x)^{(4)/(3)} = 64

Divide by 4 both sides we have;


(3-x)^{(4)/(3)} =16

or


3-x = (16)^{(3)/(4)

Using exponent rules;


a^{(n)/(m)} = (\sqrt[m]{a})^n

then;


3-x =( \sqrt[4]{16})^3

Simplify:


3-x = (2)^3

or


3-x = 8

subtract 3 from both sides we have;


-x = 5

Divide both sides by -1 we get


x = -5

Therefore, the solution for the given equation is, -5



User Hu Qiang
by
5.3k points